First records of Hysterothylacium pelagicum (Anisakidae) and Toxocara alienata (Toxocaridae) from Peru - Gomez-Puerta, Luis A. (2014)
Two ascaridoid nematodes are recorded by Peru: Hysterothylacium pelagicum parasitizing to common dolphinfish (Coryphaena hippurus) from a market of Lima and Toxocara alienata in a collared peccary (Pecari tajacu) from Iquitos. Likewise, it is made a morphological description of the nematodes.